Effect of foliar application of 2, 4‐D and calcium on red‐skinned potato cultivars. (11th December 2020) - Qin, Ruijun; Moparthi, Swarnalatha; Feldman, Max; Charlton, Brian; Sathuvalli, Vidyasagar
Abstract: Applications of the plant growth regulator 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) and calcium (Ca) are often used to improve the tuber skin quality of red potatoes. Field trials were conducted at Klamath Falls, OR in 2004 and 2005 to evaluate the effect of foliar applications of 2, 4‐D and Ca on yield components, specific gravity, and the tuber skin color of four red‐skinned potato cultivars (Red LaSoda, Mazama, Cherry Red, and Rio Rojo). Skin color was evaluated using a Konica Minolta colorimeter at three‐time points during storage. Treatments of either 2, 4‐D or Ca did not affect total tuber yield. However, 2, 4‐D increased the proportion of tubers less than 170 g potato. When compared to non‐treated potato plants, 2, 4‐D resulted in darker tuber skin with increased red pigmentation. Foliar application of Ca did not affect the tuber yield nor skin color. Calcium addition (in a form of CaCl2 ) decreased specific gravity possibly due to the chloride component. All potato cultivars exhibited color fading throughout the 6‐month storage period. Our data support the evidence that foliar application of 2, 4‐D effectively enhances the color of most red‐skin potatoes, whereas foliar application of Ca may be not necessary in soils with adequate Ca supply. Core Ideas: 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) reduced potato size but did not impact yield. 2, 4‐D enhanced skin colors of red potatoes. Calcium application did not influence skin color and yield of red potatoes. Calcium decreased tuber specific gravity in soils with adequate Ca supply. Skin color faded during storage regardless of the potato cultivar.